Kurikulum Berbasis Moderasi pada Program Studi Pendidikan Bahasa Arab di Perguruan Tinggi Swasta Aceh - Hasiolan; Munawar Ridho (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the implementation process of the Arabic Language Teaching Program curriculum based on Religious Moderation in private Islamic universities in Aceh. The focus of this research covers all stages, from planning, and implementation, to curriculum evaluation. This study also aims to identify the supporting and inhibiting factors encountered during the implementation process.  The research method used is qualitative with data collection techniques through observation, interview, and documentation. Data analysis uses the Miles and Huberman model. The results of the study show that the curriculum of the Arabic Language Teaching Program based on Religious Moderation has been well implemented in private Islamic universities in Aceh. The implementation of the curriculum focuses on the development of religious moderation values, which are reflected in every stage, from planning to evaluation. These religious moderation values are not only explicitly included in the curriculum, but also internalized through various academic activities on campus. This curriculum aims to produce students who have a deep understanding of the importance of religious moderation in the context of daily life. However, this study also identifies several factors that affect the implementation of the curriculum, both internally and externally. Supporting factors include support from university management and lecturer commitment while inhibiting factors are related to limited resources and challenges in organizing academic activities. This research contributes to understanding the application of religious moderation-based curriculum in Islamic higher education, especially in Aceh.